Penerapan Metode Token Ekonomi sebagai Intervensi untuk Meningkatkan Motivasi Belajar Siswa Slow Learner: Single Case Study di SD Muhammadiyah 1 Giri - Adinda Regita Pramesthi (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
The learning motivation of slow learner students tends to be low due to cognitive limitations, less engaging learning experiences, and the lack of positive reinforcement, thus requiring adaptive and sustainable interventions. This study focuses on how the implementation of the token economy method can enhance motivation, engagement, and learning behavior of slow learner students with speech delay in elementary school, as well as examining its effectiveness in influencing behavioral change. The study employed a quantitative approach using a single case study A-B-A’ design, which allows systematic observation of behavioral changes through pre-intervention, intervention, and post-intervention phases. The findings indicate a significant improvement in participation, persistence, and task completion, along with a reduction in negative behaviors such as task refusal and crying during the intervention phase. These improvements were maintained in the post-intervention phase despite the reduced intensity of token reinforcement, indicating a shift from extrinsic to intrinsic motivation. Trend analysis of the data reveals consistent and stable improvement across all phases, confirming the effectiveness of the token economy method as a behavioral intervention. The novelty of this study lies in the specific application of the token economy to slow learner students with speech delay through a single-subject approach, providing an in-depth and contextual understanding of motivational changes. The findings contribute theoretically to the reinforcement of the behavioristic approach and practically offer an alternative adaptive learning strategy for inclusive education at the elementary level.